Antrodia cinnamomea—An updated minireview of its bioactive components and biological activity. Issue 8 (4th June 2019) - Ganesan, Nagarajan; Baskaran, Rathinasamy; Velmurugan, Bharath Kumar; Thanh, Nguyen Chi
Abstract: Antrodia cinnamomea or Antrodia camphorata is a distinctive mushroom of Taiwan, which is being used as a traditional medicine to treat various health‐related conditions. More than 78 compounds have been identified in A. cinnamomea . Large numbers of phytochemical studies have been carried out in A. cinnamomea due to the high amount of terpenoids. Besides that, the extracts and active components of A. cinnamomea were reported to have various biological activities including hepatoprotective, antihypertensive, antihyperlipidemic, anti‐inflammatory, antioxidant, antitumor, and immunomodulatory activities. In this review article, we have summarized the recent findings of A. cinnamomea and its molecular mechanisms of action in various disease models. Practical applications: A. cinnamomea, medicinal fungus used in traditional medicine in Taiwan also possess high market value. Aim of the present review is to highlight the compounds present in A. cinnamomea and their different pharmacological activities in preventing/cure various diseases/disorders . A. cinnamomea can be potentially developed into health foods or drugs. Abstract : A. cinnamomea, an edible Taiwanese mushroom is considered as important natural resources due to its medicinal and biological properties. A. cinnamomea possess various biological activities including hepatoprotective, anti‐inflammatory, antioxidant, and antitumor activities.